Interferon γ release assay (IGRA) testing in mycobacterium tuberculosis screening prior to anti-tnf treatment: experience across 3 medical specialities. (13th March 2011) - Foster, R A; Shah, M; Hale, M; Grant, W; Abdulrehman, A; Kuet, K P; Wright, A; Robinson, K; Mark, P; Butler, L; Gawkrodger, D; McAlindon, M; et al.
Abstract : Introduction: Anti-tumour necrosis factor (anti-TNF) agents are important treatments for a range of inflammatory conditions but are associated with a fivefold increase risk of tuberculosis (TB). Newer tests based on T cell interferon γ release (IGRA) may aid diagnosis of TB. Aim: To assess the impact of IGRA testing on TB screening in patients awaiting anti-TNF therapy. Methods: 'Quantiferon' (Celestis) IGRA blood testing was performed as part of TB screening prior to anti-TNF therapy. Results were reported as positive, indeterminate (and therefore repeated) and negative. Infectious Disease assessment was recommended for positive or 2 indeterminate Quantiferon results, CXR changes or other protocol-identified TB risk. Results: 134 patients were screened (median age 47). Diagnoses: Inflammatory Bowel Diseases disease 51, Inflammatory arthropathy 63, Psoriasis 16, other 3. 91 were on immunomodulators (IM). 116 patients received anti-TNF agents. 124/134 had a Quantiferon test. 108 were negative; 8 were indeterminate (negative on repeat), of whom 7 were on IMs. 5 had 2 indeterminate results (4 on IMs). 3 had a positive test, 2 an abnormal CXR and 1 had no identified TB risk factors. Antituberculous therapy (anti-TBRx) was given to 6 patients prior to anti-TNF treatment: 3 with positive Quantiferon results, 2 negative (strong family history), 1 no test (abnormal CXR). 5 patients had CXR findings (Quantiferon negative 2; indeterminate followed by a negative 1; positive 1; not done 1). The latter 2 received anti TBRx. The screening proforma led to anti TBRx in 6 patients prior to anti-TNF therapy. In 1, the Quantiferon test was the only indicator of TB risk. After a median follow-up of 28 weeks, no patients had developed TB. Conclusion: IGRA testing aids decision making in patients awaiting anti-TNF therapy as part of a screening protocol. 1 patient of 134, not identified by other screening methods, who required prior anti TBRx, was identified in this way. Clinical risk assessment is an independent reason for anti TBRx. Longer follow-up and costing of alternatives is needed to establish the validity of this strategy.